Menjaga Identitas ditengah Keberagaman: Komunitas Bali di Kota Padang - Naserd, Yolanda Febriani; Yuliana, Yuliana (Journal of Moral and Civic Education, 2025)
This study aims to describe how the Balinese community in Padang City maintains their cultural identity amid the strong dominance of the local Minangkabau culture. Using a qualitative descriptive approach, data was collected through in-depth interviews with traditional leaders, religious leaders, and members of the Balinese community. The results of the study show that cultural preservation is carried out through religious practices such as the Manusia Yadnya ceremony, which includes baby birth rituals (otonan), life rituals (pawiwahan and mepandes), and death rituals (ngaben). The community also maintains a patrilineal kinship system, although it has undergone adaptation in the local context. In the field of education, Balinese Hindu values are instilled through non-formal education at Pura Jagadnatha. Adaptation strategies are implemented through active social interaction, participation in interfaith organizations, and integration into community life. This study confirms that the preservation of minority cultural identity can proceed harmoniously when accompanied by an open and collaborative attitude toward the majority environment, and serves as an important contribution to strengthening multicultural values in Indonesia.